Plastic shell structure for improving battery consistency
By setting an acid storage tank on the non-pressure surface of the battery plastic case structure and diffusing sulfuric acid through the side of the partition, the problem of insufficient oxygen recombination reaction in the middle of the battery is solved, the cycle performance and stability of the battery are improved, and thermal runaway is reduced risk.
Patent Information
- Application Number
- CN202411397889.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-10
AI Technical Summary
The plastic shell structure of the lead-acid battery in existing electric vehicles has an excessive volume of single grids on both sides due to the expansion of the electrode group, which leads to poor circulation performance and risk of thermal runaway, and the oxygen composite reaction of the middle four grids is insufficient.
Design a plastic shell structure that improves battery consistency. By setting acid storage tanks on both sides of the shell, dilute sulfuric acid liquid is stored, and diffused to the middle through the separator side to increase the amount of sulfuric acid in the middle, and the battery is increased cycling performance and saturation.
It improves the cycling performance of the battery, reduces the risk of thermal runaway from the battery caused by too low saturation, and ensures the stable operation and service life of the battery.
Smart Images

Figure CN119297490A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electric vehicle batteries, and in particular relates to a plastic shell structure for improving battery consistency. Background Art
[0002] Lead-acid batteries for electric vehicles use multiple pole groups arranged in series and are tightly packaged in a plastic shell structure. The tight packaging method improves the cycle life of the battery, but the middle pole group has a large outward expansion force, which causes the two outermost pole groups to expand outward, resulting in bulging of both sides of the plastic shell containing the pole groups, and the volume of the cells on both sides increases. After the pole groups are tightly assembled, they are activated by adding acid and charging, and finally a finished battery is obtained that can be used by customers. However, the increase in the volume of the cells on both sides of the finished battery causes the acid content in the cells to exceed that of the four cells in the middle, making it impossible to undergo oxygen recombination reaction, resulting in the cycle performance of the pole groups on both sides being weaker than that of the four cells in the middle. The performance decay of the pole groups on both sides accelerates the failure of the battery.
[0003] like Figure 4 The figure shows a traditional plastic shell structure of a power lead-acid battery. Since the pressure surface during pole group assembly is toward the width direction of the plastic shell, the plastic shell partitions will inevitably be subjected to the force of pole group expansion, causing the side walls to expand and deform, resulting in the volume of the cells on both sides being larger than the four cells in the middle, making the acid content and saturation of the two cells of the finished battery larger than the four cells in the middle, causing the cells on both sides to fail first.
[0004] To this end, we propose a plastic shell structure that improves battery consistency to solve the problems existing in the existing technology, so that it can not only improve the battery's cycle performance, but also reduce the risk of battery thermal runaway caused by low saturation. Summary of the invention
[0005] The purpose of the present invention is to provide a plastic shell structure that improves battery consistency. By increasing the acid content of the middle single cell, the single cell barrier saturation is increased, which can not only improve the cycle performance of the battery, but also reduce the risk of thermal runaway of the battery caused by low saturation, so as to solve the problems raised in the above background technology.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] A plastic shell structure for improving battery consistency, comprising a shell with an open upper end, a plurality of baffles fixed inside the shell for assembling and separating a plurality of pole groups, a plurality of acid storage tanks arranged on the pressure surfaces on opposite sides of the shell, side walls fixed on the other two sides of the shell, a plurality of single cells for storing pole groups formed between the plurality of baffles and the side walls and the shell, no acid storage tanks in the single cells at the two ends of the shell, acid storage tanks correspondingly arranged at both ends of the plurality of single cells located in the middle, and sulfuric acid liquid stored in the acid storage tanks.
[0008] Preferably, the acid storage tank is located in the middle of the single cell, and the acid storage tanks on both sides of the single cell are symmetrically arranged.
[0009] Preferably, the sulfuric acid liquid in the acid storage tank is set to dilute sulfuric acid, and the concentration of the dilute sulfuric acid is set to 36%-38%.
[0010] Preferably, the number of the baffles is five, and the five baffles are equidistantly distributed inside the shell, and the baffles are arranged parallel to the side walls.
[0011] Preferably, the shell is provided with a plastic shell, a convex edge is integrally formed on the upper end of the shell, and the upper surface of the baffle is flush with the upper surface of the convex edge.
[0012] Preferably, the acid storage tank is arranged in a rectangular shape, and the volume of the acid storage tank is designed according to the expanded volume of the cells at both ends, so that the consistency of the electrochemical performance of each cell is improved.
[0013] Preferably, after the cluster is assembled, the sulfuric acid in the acid storage tank diffuses through the side of the baffle to the middle of the baffle, increasing the amount of sulfuric acid in the middle of the pole group.
[0014] Preferably, the corners of the single cells at both ends away from the acid storage tank are set as arc angles, the convex edge and the shell are set in steps, and the inner wall of the convex edge is flush with the inner wall of the shell.
[0015] Preferably, the side wall is configured as a sheet made of one of polypropylene, polymethyl methacrylate, ABS engineering plastics and cellulose acetate, and the side edge of the side wall is welded to the side edge of the shell.
[0016] Preferably, reinforcing ribs are embedded inside the side wall, and the reinforcing ribs are arranged in a cross-shaped or X-shaped shape.
[0017] The plastic shell structure for improving battery consistency proposed by the present invention has the following advantages compared with the prior art:
[0018] 1. The present invention arranges acid storage tanks on the non-pressure surfaces on both sides of the shell. The non-pressure surfaces are less affected by the pole group expansion force, and the addition of acid storage tanks will not have a significant impact on the shell strength. The acid storage tanks are arranged in the middle position, and the acid storage tanks on both sides of the shell are symmetrical, thereby increasing the acid content and saturation of the middle single cell. In addition, since the battery is tightly assembled, the pressure surface direction of the shell exerts a greater force on the pole plates and the baffles, which often causes a greater resistance to sulfuric acid diffusion in the middle part. The acid storage tank is arranged in the middle position of the non-pressure surface, and the sulfuric acid in the acid storage tank is more easily diffused to the middle part through the side of the baffle, thereby increasing the sulfuric acid in the middle position of the pole group, and increasing the amount of sulfuric acid diffused to the middle of the pole group per unit time, thereby improving the reaction efficiency of the pole group, which can not only improve the cycle performance of the battery, but also reduce the risk of thermal runaway of the battery caused by low saturation. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is a structural schematic diagram of the present invention;
[0020] Figure 2 For the present invention Figure 1 The enlarged structural diagram is shown in the figure;
[0021] Figure 3 It is a schematic diagram of the cross-sectional structure of the present invention;
[0022] Figure 4 It is a schematic diagram of the plastic shell structure of a traditional power lead-acid battery;
[0023] In the figure: 1, shell; 2, partition; 3, side wall; 4, acid storage tank; 5, convex edge. DETAILED DESCRIPTION
[0024] The following will be combined with the accompanying drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. The specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0025] The present invention provides Figure 1-3 A plastic shell structure for improving battery consistency is shown, including a shell 1 with an open upper end, a plurality of partitions 2 for assembling and separating a plurality of pole groups are fixed inside the shell 1, a plurality of acid storage tanks 4 are arranged on the pressure surfaces on opposite sides of the shell 1, and side walls 3 are fixed on the other two sides of the shell 1, and a plurality of single cells for storing pole groups are formed between the plurality of partitions 2 and the side walls 3 and the shell 1, and there are no acid storage tanks 4 in the single cells at the two ends of the shell 1, and acid storage tanks 4 are arranged at both ends of the plurality of single cells located in the middle, and sulfuric acid liquid is stored in the acid storage tanks 4.
[0026] By arranging acid storage tanks 4 on the non-pressure surfaces on both sides of the shell 1, the non-pressure surfaces are less affected by the pole group expansion force, and the addition of the acid storage tanks 4 will not have a significant impact on the strength of the shell 1. The acid storage tanks 4 are arranged in the middle position, and the acid storage tanks on both sides of the shell 1 are symmetrical, thereby increasing the acid content and saturation of the middle single cell. In addition, since the battery is tightly assembled, the pressure surface direction of the shell 1 exerts a greater force on the pole plates and the baffle 2, which often causes a greater resistance to sulfuric acid diffusion in the middle part. The acid storage tank 4 is arranged in the middle position of the non-pressure surface, and the sulfuric acid in the acid storage tank 4 is more easily diffused to the middle part through the side of the baffle 2, thereby increasing the sulfuric acid in the middle position of the pole group, and increasing the amount of sulfuric acid diffused to the middle of the pole group per unit time, thereby improving the reaction efficiency of the pole group, which can not only improve the cycle performance of the battery, but also reduce the risk of thermal runaway of the battery caused by low saturation.
[0027] The acid storage tank 4 is located in the middle of the single cell, and the acid storage tanks 4 on both sides of the single cell are symmetrically arranged, thereby increasing the acid content and saturation of the middle single cell.
[0028] The sulfuric acid liquid in the acid storage tank 4 is set to dilute sulfuric acid, and the concentration of the dilute sulfuric acid is set to 36%-38%. By using dilute sulfuric acid as an electrolyte, it can play a stabilizing and catalytic role in the recycling of the battery, and has the characteristics of environmental protection and high efficiency. Dilute sulfuric acid has less corrosion to electrode materials at low concentrations, which helps to extend the service life of the battery cluster. In addition, dilute sulfuric acid has high ion conductivity, which helps ion transmission in the battery cluster, thereby improving the efficiency and stability of the battery.
[0029] The number of the partitions 2 is five, and the five partitions 2 are evenly distributed inside the shell 1, and the partitions 2 are arranged in parallel with the side walls 3, so that the spaces of multiple cells are consistent, ensuring the compactness of the cluster assembly and helping to make the acid content of each cell consistent.
[0030] The shell 1 is provided with a plastic shell, and a convex edge 5 is integrally formed on the upper end of the shell 1. The upper surface of the baffle 2 is flush with the upper surface of the convex edge 5. By using the plastic shell, the overall weight of the battery is reduced, which is convenient for carrying and use. At the same time, the plastic shell can provide sufficient strength to protect the internal components of the battery. The plastic shell has good corrosion resistance to general acids, alkalis, salts and greases, which is much better than metal materials and some inorganic materials. This enables the plastic shell structure to maintain a long service life in various environments. In addition, the plastic shell has high insulation, which can effectively prevent current leakage and ensure the safe operation of the battery.
[0031] The acid storage tank 4 is arranged in a rectangular shape, and the volume of the acid storage tank 4 is designed according to the volume expansion of the cells at both ends, so that the electrochemical performance consistency of each cell is improved, and the sulfuric acid in the acid storage tank 4 is more easily diffused to the middle through the side of the baffle 2, thereby increasing the sulfuric acid in the middle position of the pole group, so that the acid content and saturation of the four middle cells are balanced.
[0032] After the cluster is assembled, the sulfuric acid in the acid storage tank 4 diffuses to the middle of the barrier 2 through the side of the barrier 2, increasing the amount of sulfuric acid in the middle of the pole group. Increasing the amount of sulfuric acid in the middle of the pole group can ensure that the sulfuric acid is more evenly distributed in the battery cluster, thereby improving the ion transfer efficiency between the electrodes; during the operation of the battery, due to the electrochemical reaction, the sulfuric acid in the electrolyte will be continuously consumed, resulting in a gradual decrease in concentration. By increasing the amount of sulfuric acid in the middle of the pole group in the acid storage tank 4, this consumption can be effectively compensated and the electrolyte concentration gradient caused by the reaction can be reduced. This helps to maintain the stable operation of the battery and extend its service life; the battery cluster is composed of multiple single cells, and its overall performance depends on the consistency between the single cells. Increasing the amount of sulfuric acid in the middle of the pole group can ensure that the electrolyte environment and state of each single cell are as consistent as possible, thereby reducing the performance difference between the single cells and improving the overall performance of the entire battery cluster; in the battery cluster, the uneven distribution of electrolytes may cause some electrodes to overload, thereby affecting the reliability of the battery. By increasing the amount of sulfuric acid in the middle of the pole group, this situation can be avoided, ensuring that the battery maintains good performance stability during long-term operation.
[0033] The corner of the single cell at both ends away from the acid storage tank 4 is set to an arc angle, the convex edge 5 is set in a step-like manner with the shell 1, and the inner wall of the convex edge 5 is flush with the inner wall of the shell 1. Setting the corner of the single cell at both ends away from the acid storage tank 4 to an arc angle, and the convex edge 5 is set in a step-like manner with the shell 1 and the inner wall is flush, can not only improve the structural strength and safety of the battery, but also simplify the production process, promote uniform distribution of electrolyte, reduce material stress, enhance thermal management performance, and improve space utilization.
[0034] The side wall 3 is configured as a sheet made of one of the materials selected from polypropylene, polymethyl methacrylate, ABS engineering plastics and cellulose acetate, which can not only improve the structural strength and safety of the battery, but also simplify the production process, promote uniform distribution of electrolyte, reduce material stress, enhance thermal management performance, and improve space utilization. The side edge of the side wall 3 is welded to the side edge of the shell 1, and the welding technology is used to ensure the seamless connection between the side wall 3 and the shell 1, thereby enhancing the compressive resistance and stability of the overall structure. This fixing method can effectively disperse external pressure and reduce the risk of damage.
[0035] The side wall 3 is embedded with reinforcing ribs in a cross-shaped or X-shaped configuration. The reinforcing ribs can effectively increase the rigidity and strength of the side wall 3, while also saving material usage, reducing weight, and reducing costs. In the design of plastic parts, reinforcing ribs can not only prevent deformation and improve plastic flow, but also increase the strength and rigidity of plastic parts by increasing the number of reinforcing ribs rather than the wall thickness.
[0036] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A plastic shell structure for improving battery consistency, characterized by: The invention comprises a shell (1) with an open upper end, a plurality of baffles (2) for assembling and separating a plurality of pole groups being fixed inside the shell (1), a plurality of acid storage tanks (4) being arranged on the pressure surfaces on opposite sides of the shell (1), a side wall (3) being fixed on the other two sides of the shell (1), a plurality of single cells for storing pole groups being formed between the plurality of baffles (2) and the side wall (3) and the shell (1), the single cells at the two ends of the shell (1) having no acid storage tanks (4), and the two ends of the plurality of single cells in the middle having acid storage tanks (4) correspondingly arranged, and sulfuric acid liquid being stored in the acid storage tanks (4).
2. A plastic shell structure for improving battery consistency according to claim 1, characterized in that: The acid storage tank (4) is located in the middle of the single cell, and the acid storage tanks (4) on both sides of the single cell are symmetrically arranged.
3. A plastic shell structure for improving battery consistency according to claim 2, characterized in that: The sulfuric acid liquid in the acid storage tank (4) is set to be dilute sulfuric acid, and the concentration of the dilute sulfuric acid is set to 36%-38%.
4. A plastic shell structure for improving battery consistency according to claim 3, characterized in that: The number of the partitions (2) is five, and the five partitions (2) are equidistantly distributed inside the shell (1), and the partitions (2) are arranged in parallel with the side walls (3).
5. A plastic shell structure for improving battery consistency according to claim 4, characterized in that: The shell (1) is provided with a plastic shell, and a convex edge (5) is integrally formed at the upper end of the shell (1), and the upper surface of the baffle (2) is flush with the upper surface of the convex edge (5).
6. A plastic shell structure for improving battery consistency according to claim 5, characterized in that: The acid storage tank (4) is arranged in a rectangular shape, and the volume of the acid storage tank (4) is designed according to the expanded volume of the cells at both ends, so that the consistency of the electrochemical performance of each cell is improved.
7. A plastic shell structure for improving battery consistency according to claim 6, characterized in that: After the cluster is assembled, the sulfuric acid in the acid storage tank (4) diffuses through the side of the baffle (2) to the middle of the baffle (2), thereby increasing the amount of sulfuric acid in the middle of the pole group.
8. A plastic shell structure for improving battery consistency according to claim 7, characterized in that: The corners of the single cells at the two ends away from the acid storage tank (4) are arranged as arc angles, the convex edge (5) and the shell (1) are arranged in steps, and the inner wall of the convex edge (5) is flush with the inner wall of the shell (1).
9. A plastic shell structure for improving battery consistency according to claim 8, characterized in that: The side wall (3) is configured as a sheet made of one of polypropylene, polymethyl methacrylate, ABS engineering plastics and cellulose acetate, and the side edge of the side wall (3) is welded to the side edge of the shell (1).
10. A plastic shell structure for improving battery consistency according to claim 9, characterized in that: Reinforcing ribs are embedded inside the side wall (3), and the reinforcing ribs are arranged in a cross-shaped or X-shaped manner.